PENGARUH BUDAYA, KELAS SOSIAL, KELUARGA DAN SITUASI TERHADAP PENGAMBILAN KEPUTUSAN KONSUMEN DALAM PEMBELIAN PERUMAHAN DI KOTA JAMBI (STUDI KASUS PADA DEVELOPER DAN REAL ESTEAT PT NIAGA GUNA KENCANA JAMBI) - Ahmad Tarmizi (Universitas Batanghari Jambi, 2013)
PT. Niaga Kencana Guna (NGK) one floating housing is enough known in the Development of quality housing, connection with the marketing strategy. How does culture (X1), social class (X2), Family (X3), Situation (X4) and decision making (Y) consumers in the purchase of housing PT. Niaga Kencana Guna (NGK).T value at the Cultural variables ( X1 ) is 2.844 with a significance level of 0.005 . Because the 2,844 t value > t table value and level of significance 1.661 0.005 < α = 0.05 significance probability , t Value on Social Class variable ( X2 ) is 3.204 with a significance level of 0.002 . Because the t value 3.204 > t table value and level of significance 0.002 1.661 < α = 0.05 significance probability , t value in the variable Family ( X3 ) is 2.231 with a significance level of 0.028 . Because the t value 2.231 > 1.661 and table value of t 0.028 significance level < probability of significance α = 0.05 , t value in a variable situation ( X4 ) is 3.928 with a significance level of 0.000 . Because the t value 3.928 > 1.661 and table value of t 0.000 significance level < probability of significance α = 0.05 , then Ho is rejected and Ha accepted . This means that the variable situation individually positive and significant impact on consumer purchase decisions .Keyword : influence, decisions, housing